A terminal distribution network black-start optimization method based on pruning algorithm considering distributed generators - Yuhong Zhu; Yongzhi Zhou; Zhe Wang; Chenlong Zhou; Bing Gao (Energy Reports, 2022)
The main objective of the black-start in a terminal distribution network is restoring the regional distribution network in a blackout. Aiming at the problem that there are multiple optimization objectives in the process of black start, a black start model with comprehensive consideration is established, considering the minimum switching operation cost, maximum recovery efficiency and priority start of important load. Then, the constraints of voltage and frequency stability of the distribution network in black-start are put forward. Aiming at the problem that heuristic algorithm such as binary particle swarm optimization cannot get the global optimal solution, a black-start method based on pruning algorithm is proposed, which has higher efficiency than traditional algorithm as well as the ability to search the global optimal method. Finally, the efficiency of the above method is verified in the terminal distribution network of a coastal mountain county.